Wigner function description of a qubit-oscillator system - Allen, James; Zagoskin, A.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We derive the Bloch-type equations of motion for the Wigner function of a qubit nonlinearly coupled to a linear oscillator, and investigate their usefulness in the quantum-classical transition regime.